Urban stakeholder analysis for food waste prevention and reduction in Sri Lanka - Aheeyar, Mohamed M. M.; Jayathilake, Nilanthi; Bucatariu, C.; Reitemeier, Maren; Drechsel, Pay (FAO; IWMI, 2023)
Mapping stakeholders and their potential roles for prevention and reduction of food waste (FW) supports a coherent, coordinated and complementary approach to quantification, causes identification and scaling up of feasible solutions for significant returns on investment. State and nonstate stakeholders were mapped in selected municipalities: Colombo metropolitan area (Colombo, Sri Jayewardenepura-Kotte, Negombo, Kaduwela and Moratuwa municipal council areas), Jaffna, Kandy, Batticoloa, Kurunegala and Galle. Stakeholders were grouped into four clusters: producers, enterprises/food business operators, private/public/civil society organizations and households. The stakeholders’ maps guided sensitization and capacity-building sessions whose conclusions fed into the preparation of the National Roadmap on Urban Food Waste Prevention and Reduction for Households, Food services, Retailers and Wholesalers launched on 17 August 2021. According to the analysis, the institutions working on food and/or (bio-)waste can be divided into governmental, semi-governmental, private, and non-governmental. Food safety, quality control and waste management in Sri Lanka is under the umbrella of the central government, provincial council (PC) and local authorities(LAs) that cover governance (e.g. policies and regulations), production, trade, input supply, services, welfare support and research. However, duties and responsibilities are, sometimes, crosscutting and interrelated with overlaps that can lead to poor coordination. An array of institutions at central and provincial levels are engaged to strengthen the food production sector in Sri Lanka. The existing inter-institutional coordination mechanism could be improved. The coordination for knowledge generation and dissemination between national and provincial systems should be strengthened. The report was produced for the project Innovative approaches to reduce, recycle and reuse FW in urban Sri Lanka that was implemented under the oversight of the Ministry of Urban Development and Housing, in collaboration with the Food and Agriculture Organization of the United Nations (FAO) and the International Water Management Institute (IWMI) from June 2019 to August 2021.